RESPOSTA DO ARROZ À ADUBAÇÃO COM ZINCO - Coutinho, Edson L. M.; Otsubo, Auro Akio; Martins, Celso de Souza; Childz, Grisel Fernandez (REVISTA DE AGRICULTURA, 2015)
RESPOSTA DO ARROZ À ADUBAÇÃO COM ZINCO